Europe's mechanism for countering the risk of carbon leakage - Aleksandar Zaklan; Bente Bauer (Deutsches Institut für Wirtschaftsforschung (DIW), 2015)
The EU's Emissions Trading System (EU ETS) is a regional cap-and-trade program in a world with no binding international climate agreement. This climate regulation may induce a relocation of production away from Europe, with potentially negative consequences for the European economy. This relocation could lead to carbon leakage, i.e. a shift of greenhouse gas emissions from Europe into regions with less stringent climate policy. In response, installations in sectors deemed to be vulnerable receive compensatory free emissions allowances. The European Commission compiles a carbon leakage list of vulnerable sectors. The current mechanism distinguishes two levels of leakage risk. The criteria used lead to the majority of European industry regulated under the EU ETS benefiting from the additional compensation. Whereas industry representatives argue that the current level of compensation should be maintained if not increased, the evidence suggests that under the current framework overcompensation may occur. We describe the mechanism currently used to address the risk of carbon leakage in Europe, and for comparison outline the more differentiated system of assessing leakage risk used in the Californian cap-and-trade system. Applying such a more differentiated mechanism in the European context would lead to a re-distribution of compensation from sectors with an intermediate level of leakage risk to high-risk sectors.
Keywords: 330